Fungal infection models: Current progress of ex vivo methods. Issue 10 (4th August 2019) - Maciel Quatrin, Priscilla; Flores Dalla Lana, Daiane; Andrzejewski Kaminski, Taís Fernanda; Meneghello Fuentefria, Alexandre
Summary: Experimental alternative ex vivo models that simulate infectious processes in vivo are of fundamental importance for the evaluation of new drugs, since in some cases, their execution does not depend on the approval of an ethics committee in research. Although studies using alternative infectious models to evaluate the efficacy of antifungal molecules have been increasingly described and reported, there is no critical consensus that establishes the most appropriate ones regarding the type of infection. Numerous studies contemplate ex vivo protocols of fungal infections on nails, corneas, dentinal tubules and skin and reveal counterpoints and concordances not yet finely confronted. In this minireview, we propose a critical analysis of the main ex vivo models of fungal infections for the evaluation of new antifungal candidates for both topical and systemic use, as opposed to the advantages and disadvantages of the traditional in vivo models employed in preclinical research.